Influência de diferentes protocolos de exercício e da dieta hiperlipídica sobre o tecido adiposo, perfil lipídico e receptor CB1 do sistema endocanabinóide - Rosante, Marisa Cristina (Universidade Federal de São Carlos, 2011)
The purpose of this study was to investigate the effects of high-fat diet and swimming and resistance training in the adipose tissue, endocannabinoid system and lipid profile in obese rats. Wistar adult male rats were divided into 6 groups (n = 10 per group): sedentary chow diet (SP); sedentary high-fat diet (SH); swimming chow diet (NP); swimming high-fat diet (NH); resistance training chow diet (FP); resistance training high-fat diet (FH). After three weeks feeding on a chow diet or high-fat diet, the animals started the exercise protocols. The NP and NH groups swam 60 minutes/day, five days a week, with a constant overload of 5% body weight during 8 weeks in tanks of 50 cm of height and 30 cm of diameter, for 8 weeks. The groups FP and FH started the resistance training with weights tied to their tails, once every three days for 8 weeks. The animals of SP and HS groups remained sedentary and fed their respective diets. After this period all animals were sacrificed by decapitation and tissues dissected, weighed and immediately stored at -80 º C. High-fat diet increased body weight gain, relative weight of adipose tissues (epididymal, retroperitoneal, visceral and subcutaneous) and adipose tissue area (epididymal, retroperitoneal and visceral). It also increased the fat percentage of all adipose tissues and liver, and increased gene expression of CB1 receptor. The trained groups, both resistance training and swimming, presented lower values of adipocyte area, benefits in lipid profile, lower percentage of fat in the adipose tissue and liver, lower body weight gain, and lower values for gene expression the CB1 receptor. Thus our results indicate the potential benefits of the resistance training and swimming as non pharmacological alternatives to control the deleterious effects of high-fat diet on adipose tissue, lipid profile, lipid content of tissues and control of the endocannabinoid system imbalance caused by high-fat diet.
Keywords: Fisiologia humana; Obesidade; Exercícios físicos; Receptor CB1; Sistema endocanabinóide; Tecido adiposo; Treinamento de força; Natação; PPARy; Perfil lipídico; Obesity; Resistance training; Swimming; Receptor CB1; Endocannabinoid system, PPARy; Adipose tissue; Lipid profile; CIENCIAS BIOLOGICAS::FISIOLOGIA